2016
DOI: 10.1111/joss.12215
|View full text |Cite
|
Sign up to set email alerts
|

Korean Consumer Evaluation of Various Foods Using Four Different Texture Lexicons

Abstract: Texture is an important food quality contributing consumers' acceptance of foods. Texture terminologies have been developed in various languages. While comparative studies using different languages are becoming a trend, there is not a fully developed Korean texture lexicon existing. There was a study in 1980s which developed Korean texture terms using cooked rice, noodles and Kimchi. Since then, there was no further study using this texture terms list nor developing new texture terms in Korea. The aims of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Generating a method of sensory profiling and measuring consumer acceptability are the starting points needed to develop products to satisfy the quality standards that many consumers demand (Varela & Ares, ). Several studies have reported the descriptive profiles and/or consumer acceptability of Korean foods (Chambers, Lee, Chun, & Miller, ; Chang, Kwak, Yoo, & Lee, ; Jang, Kim, Lim, & Hong, ; Kim & Lee, ; Kwak, Ahn, Kim, & Lee, ). For doenjang , Kim, Hong, Song, Shin, and Kim () described the sensory characteristics and consumer acceptability of doenjang and reported that consumer acceptability was positively affected by sweetness and umami and negatively influenced by saltiness, meju , soy sauce, and fermented fish sauce flavors.…”
Section: Introductionmentioning
confidence: 99%
“…Generating a method of sensory profiling and measuring consumer acceptability are the starting points needed to develop products to satisfy the quality standards that many consumers demand (Varela & Ares, ). Several studies have reported the descriptive profiles and/or consumer acceptability of Korean foods (Chambers, Lee, Chun, & Miller, ; Chang, Kwak, Yoo, & Lee, ; Jang, Kim, Lim, & Hong, ; Kim & Lee, ; Kwak, Ahn, Kim, & Lee, ). For doenjang , Kim, Hong, Song, Shin, and Kim () described the sensory characteristics and consumer acceptability of doenjang and reported that consumer acceptability was positively affected by sweetness and umami and negatively influenced by saltiness, meju , soy sauce, and fermented fish sauce flavors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the methodology employed to this end successfully uncovered and accommodated differences rooted on subjects' sensory and professional expertise, culture and product familiarity. This brings important contributions to the sensory optimization of hibiscus tea production and the marketing of hibiscus products in international markets, as the vital role played by cross‐culturally developed and validated, multilingual and easy‐to‐use lexicons encompassing the vocabulary of trained panelists, untrained professionals and consumers in such activities is increasingly acknowledged (Andani et al, ; Hayakawa et al, ; Kim & Lee, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, food producing and trading companies do not always have the possibility to train or get access to trained panelists. The sensory vocabulary used by untrained professionals, or even by consumers, may also provide relevant product descriptions for marketing research, sales and customer support (Hayakawa et al, ; Kim & Lee, ). Moreover, its reliability can be assessed by comparison against sensory lexicons developed by trained panelists (Ares et al, ; Blancher, Clavier, Egoroff, Duineveld, & Parcon, ; Worch, Lê, & Punter, ).…”
Section: Introductionmentioning
confidence: 99%
“…The panel has been used to develop sensory lexicons and to evaluate a number of commercial and experimental products including research on thickened beverages (Matta et al, ), as well as other liquids such as soy sauce (Cherdchu & Chambers, ), coffee (Chambers et al, ), green tea (Lee, Chambers, & Chambers, ), and other products such as cheese (Talavera & Chambers, ). Kim and Lee () found that a texture lexicon developed by a similarly trained descriptive sensory panel in the United States was shown to be valid when translated into another language (Korean).…”
Section: Methodsmentioning
confidence: 99%